Healthcare values and potential uses of the new Hungarian apple varieties on the basis on fruit analysis - Ficzek, G.; Ladányi, M.; Radeczky, Zs.; Tóth, M. (International Journal of Horticultural Science, 2013)
Biological active compounds and valuable characteristics of some apple varieties and candidates were measured in our trials. Fruits of ’Rosmerta’, ’Hesztia’, ’Cordelia’ and ’Artemisz’ are recommended to enrich the Hungarian assortments for fresh consumption and choice of new tastes. Based on examined parameters it can be assumed that novel Hungarian resistant varieties are suitable for juice and fruit concentrate production, and due to high pectin content of their remaining pomace these varieties can be raw material of pectin production as well as they are also suitable for jam production mixed with other fruit species. Furthermore, functional food industrial product having high quality can be produced by using novel resistant varieties because of their high pectin and polyphenol content. Beside of their high market value their suitability for growing among orchard conditions is confi rmed by lower costs of production because of less plant protection treatments.